1993
DOI: 10.1109/23.273479
|View full text |Cite
|
Sign up to set email alerts
|

Radiation response of silicon on diamond (SOD) devices

Abstract: Field effect msistors are fabricated on two types of Silicon-On-Diamond (SOD) structures and their radiation response is studied. The results are compared with the radiation response of simultaneously fabricated SIMOX devices. The feasibility of fabricating field effect transistors on SOD structure is demonstrated for the first time and the extreme radiation hardness of such a structure is also verified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(11 citation statements)
references
References 3 publications
1
10
0
Order By: Relevance
“…Annamali et al were the first to successfully fabricate operating Si-MOSFETs on SOD wafers. 1,8,9 A similar SOD structure with MOSFET devices was reported by Soderbarg et al 2,10,11 Gu et al scaled the SOD fabrication described in Refs. 2 to 4; 12 the same authors also reported the fabrication of integrated circuits on SOD but failed to demonstrate device or circuit logic function.…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…Annamali et al were the first to successfully fabricate operating Si-MOSFETs on SOD wafers. 1,8,9 A similar SOD structure with MOSFET devices was reported by Soderbarg et al 2,10,11 Gu et al scaled the SOD fabrication described in Refs. 2 to 4; 12 the same authors also reported the fabrication of integrated circuits on SOD but failed to demonstrate device or circuit logic function.…”
Section: Introductionsupporting
confidence: 62%
“…7 The work carried out to date on SOD has been largely focused on the fabrication and analysis of operating devices and their radiation hardness. 9,12 There has been very little work completed to actually quantify the advantages that diamond would offer in thermal management. Soderbarg et al calculated a two-dimensional temperature distribution for SOD with respect to SOI and provided a comparison of operating temperatures for Schottky diodes for both cases.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Such films have great potential for use in various semiconductor applications, especially those related to operation at high temperature or those requiring an effective heat spreading capability. The use of diamond films as buried insulators for silicon-on-insulator ͑SOI͒ materials is an interesting application of diamond as a heat spreader.…”
Section: Introductionmentioning
confidence: 99%
“…Such materials include polycrystalline diamond for use as buried insulator in silicon-on-insulator applications, for instance. 1,2 Naturally, it is of great importance to make a correct electrical characterization of the material. However, when new materials are considered interpretation of measurement data must take new effects into account.…”
Section: Introductionmentioning
confidence: 99%